Selenite supplementation in euthyroid subjects with thyroid peroxidase antibodies - Eskes, Silvia A.; Endert, Erik; Fliers, Eric; Birnie, Erwin; Hollenbach, Birgit; Schomburg, Lutz; Köhrle, Josef; Wiersinga, Wilmar M. (Clinical endocrinology (Oxford), 2014)
Summary Context Euthyroid thyroid peroxidase (TPO‐Ab)‐positive subjects are at risk for progression to subclinical and overt autoimmune hypothyroidism. Previous studies have shown a decrease in TPO‐Ab and improvement of quality‐of‐life (QoL) in L‐T4‐treated hypothyroid patients upon selenium supplementation. Objectives To evaluate in euthyroid TPO‐Ab‐positive women without thyroid medication whether selenite decreases TPO‐Ab and improves QoL. Design Randomized, placebo‐controlled, double‐blind study. Patients and methods Euthyroid (TSH 0·5–5·0 mU/l, FT4 10–23 pm) women with TPO‐Ab ≥ 100 kU/l were randomized to receive 200 mcg sodium selenite daily (n = 30) or placebo (n = 31) for 6 months. TSH, FT4, TPO‐Ab, selenium (Se), selenoprotein P (SePP) and QoL were measured at baseline, 3, 6 and 9 months. Results There were no differences in baseline characteristics between the Se group and the placebo group. During selenite supplementation, serum Se and SePP did not change in the placebo group, but increased in the Se group. TPO‐Ab and TSH did not change significantly in any group. TPO‐Ab in the Se group were 895 (130–6800) at baseline, 1360 (60–7050) kU/l at 6 months, in the placebo group 1090 (120–9200) and 1130 (80–9900) kU/l, respectively (median values with range). TSH in the Se group was 2·1 (0·5–4·3) at baseline, 1·7 (0·0–5·3) mU/l at 6 months, in the placebo group 2·4 (0·7–4·4) and 2·5 (0·2–4·3) mU/l, respectively. QoL was not different between the groups. Conclusion Six months selenite supplementation increased markers of selenium status but had no effect on serum TPO‐Ab, TSH or quality‐of‐life in euthyroid TPO‐Ab‐positive women.